The Growth of Renewable Energy in Brazil from a Global Perspective: A Systematic Review of Trends, Challenges, and Opportunities - Silva, Christian Gianelli da; Silva, Waner Wodson Aparecido Gonçalves (Brazilian Journal of Production Engineering, 2025)
This article presents a systematic literature review aimed at identifying and consolidating the main trends, challenges, and opportunities shaping the growth of renewable energy in Brazil from a global perspective. Based on the PRISMA guidelines and a qualitative and quantitative analysis of publications from 2010 to 2025, seven core studies were selected from the Scopus database, complemented by other relevant academic sources. The results highlight advances in energy storage technologies, such as pumped hydro storage (PHS), the rise of green hydrogen, the decentralization of electricity generation, and Brazil’s international leadership in the renewable sector. However, significant challenges remain, including regulatory bureaucracy, transmission infrastructure deficiencies, and socio-environmental conflicts. The study concludes that Brazil's energy transition requires greater coordination between science, public policy, and social inclusion to ensure a sustainable, fair, and competitive energy future.
Keywords: renewable energy; Brazil; energy sustainability; challenges and opportunities; systematic review